Urban Consumer Market Segmentation: A Study for Brand and Lifestyle Preferences Using The K-Means Clustering - Dwirahmawati, Retno; Nugraha, Yudi; Threezardi, Ricki; Haikal, Jerry (Journal of Innovative and Creativity, 2026)
This research to identify and analyze urban consumer market segments based on their brand and lifestyle preferences by using the K-Means Clustering algorithm. Data processing is assisted by the application of Python 3. With high technology adoption, urban consumers exhibit strong reliance on digital platforms for convenience and efficiency, including e-commerce (Shopee, Tokopedia), digital payments (QRIS), and on-demand transport/delivery services (Grab/Gojek). Consumers within these segments highly value product quality, reflecting a smart and rational purchasing approach, driven by both essential needs and the desire for personal satisfaction. Despite showing significant preference for established, prestigious, and high-quality global brands (such as Adidas, Rolex, Gucci, Tag Heuer, Nike), there is also consistent strong support for local brands, indicating a balance between global appeal and an appreciation for domestic products or authentic values. An active and health-conscious lifestyle is also characteristic, with interests in sports, running, and travel. Furthermore, preferences for complex and luxurious fragrance aromas (Musky Powdery Floral, Floral Vanilla, Citrus Aromatic, Oud Woody Smoky) highlight refined tastes and attention to personal appearance. Social media activity also indicates that urban consumers are an easily reachable audience influenced by digital trends. The findings of this study reveal diverse consumer segments, each exhibiting distinct patterns in demographics, occupation, income, hobbies, and shopping behavior. The first cluster, "Urban Modern Local Woman," characterizes women aged 40-50 with S1 education who are both employees and entrepreneurs, primarily driven by an interest in promotions when shopping. The second cluster, "The Independent Aspiring Professionals Man & Woman," targets single individuals aged 20-40 with S1 education, enjoying reading and sports as hobbies, and making purchases based on need. Furthermore, "The Sporty Urban Ambitious Man" represents men aged 20-40 with S1 education, who are also both employees and entrepreneurs, with a passion for sports and purchasing items they genuinely like. The final two clusters focus on married middle-aged men: "The Urban Professional Mature Man also Well Educated Daddy" describes men aged 40-50 with S2 education, working as private sector employees, who value product quality and enjoy a wide range of hobbies including reading, sports, traveling, music, and arts. Meanwhile, "The Classy, Sporty and Tech-Savvy Dad" also comprises men aged 40-50, with S1 education and private sector employment, who share similar hobbies but tend to shop based on competitive pricing, while being highly active on social media and adopting modern technology